2021
DOI: 10.1177/15330338211041253
|View full text |Cite
|
Sign up to set email alerts
|

Overexpression of ICAT Inhibits the Progression of Colorectal Cancer by Binding with β-Catenin in the Cytoplasm

Abstract: Inhibitor of β-catenin and T-cell factor (ICAT) was first found as a polypeptide that blocks β-catenin–TCF interaction. Abundant evidence has shown that ICAT has different functions in diverse cancers’ progression. Nevertheless, the roles it plays in colorectal cancer (CRC) have not been described. Here, we documented that ICAT expression was higher in CRC tissue than in the adjacent normal tissue and that prognosis was better in high-ICAT expression patients. The overexpression of ICAT inhibited CRC cell prol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 29 publications
2
11
0
Order By: Relevance
“…Our previous experiments showed that ICAT could inhibit the proliferation of CRC cells by binding to β-catenin in the cytoplasm. 13 However, in this study, we confirmed that ICAT could promote CRC invasion and migration, which is consistent with the premetastatic role on ICAT reported in studies of melanoma and cervical cancer. 10,12 The ICAT reflects the metastatic ability of CRC and can be developed as a potential diagnostic biomarker.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Our previous experiments showed that ICAT could inhibit the proliferation of CRC cells by binding to β-catenin in the cytoplasm. 13 However, in this study, we confirmed that ICAT could promote CRC invasion and migration, which is consistent with the premetastatic role on ICAT reported in studies of melanoma and cervical cancer. 10,12 The ICAT reflects the metastatic ability of CRC and can be developed as a potential diagnostic biomarker.…”
Section: Discussionsupporting
confidence: 92%
“…Stable cell lines overexpressing the protein of interest were developed as previously described. 13,18 Lentiviruses carrying ICAT cDNA and vector control (VC) packaged by Vigene Biosciences were transfected into the SW480 cell line following the manufacturer's instructions to construct ICAT-overexpressing cell lines and VC. Stable cell lines were selected after 2 weeks of puromycin (10 μg/ml) selection and were maintained in 1 μg/ml puromycin.…”
Section: Lentivirus Infection and Transfectionmentioning
confidence: 99%
See 1 more Smart Citation
“…ICAT was found to be a polypeptide that downregulates the expression of genes that are targeted by the Wnt pathway, such as cyclin D1 and Myc, by blocking the β-catenin-TCF interaction, which significantly reduces the growth of CRC cells and tumor formation (62). Furthermore, patients with CRC and high ICAT levels have a favorable prognosis.…”
Section: Pnu-74654 Gb1874 and Inhibitor Of B-catenin And Tcf (Icat) P...mentioning
confidence: 99%
“…Thus, we observed that catenin, beta-interacting protein 1 (inhibitor of beta-catenin and TCF [ ICAT ] or CTNNBIP1 ), an inhibitor of β-catenin is upregulated during monocyte differentiation, can enhance drug sensitivity of HL60 cells. [ 8 ] The ICAT molecule plays a crucial role in the Wnt/β-catenin signaling pathway, and in a competitive region with T-cell factor ( TCF )/lymphocyte enhancement factor ( LEF ), binds to the tandem protein and E-cadherin and inhibits Wnt signal transduction as well as intracellular adhesion, [ 9 , 10 ] which plays a critical role in tumorigenesis. Therefore, it has been observed in several studies that ICAT acts as a caner suppressor.…”
Section: Introductionmentioning
confidence: 99%